RESEARCH OF THE ASPECTS OF FOLDED STRUCTURES OF THE NORTH-WESTERN PART AT SKELYUVATSKE DEPOSIT (KRYVYI RIH BASIN) - Stetsenko, V.; Zavgorodnyaya, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The purpose of this paper is the study of morphological features of folded deformation at Skelyuvatske deposit of the Kryvyi Rig Basin. The main method of study of the morphology of folded deformation in rocks at Skelyuvatske deposit is a geological and structural mapping, which was developed for iron ore deposits and has been successfully used for deposits of the Kryvyi Rig Basin and the Kursk magnetic anomaly. In the process of geological mapping of the north-western part of Skelyuvatske deposit, certain regularity of location of various in morphology folds was discovered. It was defined that the central part of deposit is dominated by symmetrical angled limb of the folds, complicated by numerous drag folds.The angles of incidence are limb 45°. Further to the West asymmetrical inclined folds with limbs falling vertically and horizontally start to dominate. Originality. Scientific novelty is in obtaining modern accurate geological information concerning special characteristics of plicative dislocations at Skelyuvatske deposit. Practical value. The results of geological-structural mapping can be used for future planning and management of exploration and mining operations in the open-pit YuGOK.